PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PERUSAHAAN TONG TJI TEA HOUSE MEDAN - Laowo, Artemas; Sari, Inggrit Puspita (JURNAL PSYCHOMUTIARA, 2023)
The advent of the globalization era led to the rise of industrialization in Indonesia. There are many businesses that are flourishing in Indonesia, both domestic and foreign businesses. A growing number of well-run businesses will result in a growing amount of rivalry amongst businesses. Workplace motivation is one of the factors that most negatively affects an organization's ability to function overall. Strong work motivation will result in good work performance. The purpose of this study is to determine the impact of work motivation on employees at Tong Tji Tea House Medan. The research methodology used in this study is the quantitative research methodology. The study location is Tong Tji Tea House in Medan. The sample in this study consists of 51 employees of Tong Tji Tea House in Medan. The study's results show that R has a value of 0.353, which indicates that it has a significant correlation of 0.011. R square (R2).